Immediate and long-term outcomes of carotid bifurcation remodeling - А. А. Карпенко; В. Б. Стародубцев; П. В. Игнатенко; Р. А. Кужугет; И. Н. Ким; В. Н. Горбатых (Патология кровообращения и кардиохирургия, 2015)
Immediate and long-term outcomes of carotid endarterectomy (CEA) performed in 363 patients at 6 months to 4 years are presented. It was found out that when using a xenopericardial patch, the occurrence of carotid artery restenosis is significantly lower if compared with the application of a PTFE patch. In comparison with classical CEA (carotid plasty with a xenopericardial patch and PTFE), eversion CEA and CEA with autoarterial bifurcation remodeling have a significantly lower frequency of restenosis (p<0,01) during long-term follow-up.